The ashes of Waco: an investigation - Reavis, Dick J. (Simon & Schuster, 1995)
Investigation of the raid on the Branch Davidian compound in Waco, Texas in 1993, which resulted in the deaths of over seventy people including leader David Koresh, arguing that the government's actions were more the result of religious prejudice than of any suspicion of illegal activity on the part of the group